Ammoniacal Nitrogen and COD Removal Using Zeolite-Feldspar Mineral Composite Adsorbent - Ibrahim, Farah Nur Diyana; Daud, Zawawi; Abdul Latiff, Ab Aziz; Ridzuan, Mohd Baharudin; Ahmad, Zulkifli; Awang, Halizah; Marto, Aminaton (International Journal of Integrated Engineering, 2017)
The vigorous combination of  waste in landfill recognized as potential hazard source, but one distinctive problem associated with landfill is leachate. Zeolite is known as good adsorbent but the cost is relatively high. Feldspar is the most abundant mineral group in the world, forming around 60% of the earth’s crust. Due to its availability, feldspar becomes one of low cost materials.  Feldspar and zeolite is combining as an composite adsorbent in this study where there optimum ratio between this material is determined. The experimentcarried out in a series of 250 mL conical flask with varied amount of media ratio  shaken for 5 hours with 200 rpm shaking speed and at pH 7. The best ratio of feldspar and zeolite  chosen is 1:1 according to the adsorption behavior of organic constituent (COD) and ammoniacal nitrogen (NH3-N) to the media. The value of the removal percentage of COD and  NH3-N is  49% and 45% respectively and the  uptake  capacity for both contaminant is 50.14 mg/g  and 8.06mg/g respectively.  The usage of feldspar  will significantly reducing zeolite usage conventionally and consequently decresing the operational cost in leachate treatments